IrO2-RuO2-SnO2 / Ti coating titanium anode and preparation method and application thereof

By using the IrO2-RuO2-SnO2/Ti coating structure and sol-gel method on the titanium electrode, the problem of poor performance of titanium electrode in acidic oxygen evolution environment is solved, and the effect of improving catalytic activity, corrosion resistance and extending service life is achieved.

CN119859799APending Publication Date: 2025-04-22YUNNAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510093693.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing titanium electrodes are used in acid oxygen evolution environments with poor performance, high cost and short service life, mainly due to the rareness of IrO2 and RuO2, the low bond strength of coating and titanium matrix, and the large intergranular gap, the penetration of acid solution.

Method used

The IrO2-RuO2-SnO2/Ti coating structure was prepared by the sol-gel method, and SnO2 was added to improve coating activity and corrosion resistance, and the molar ratio and preparation process were optimized to form a rutile solid solution structure.

Benefits of technology

It improves the catalytic activity, corrosion resistance and comprehensive performance of the titanium anode, extends the service life and reduces material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859799A_ABST
    Figure CN119859799A_ABST
Patent Text Reader

Abstract

The invention discloses an IrO2-RuO2-SnO2 / Ti coating titanium anode and a preparation method and application thereof, and belongs to the technical field of titanium electrodes, the preparation method comprises the following steps: (1) adding a mixed solution of citric acid and ethylene glycol into a mixed solution of ruthenium trichloride and chloroiridic acid, then dropwise adding water and hydrochloric acid, and carrying out ultrasonic treatment to obtain a mixed colloidal solution; and (2) citric acid, ethylene glycol and hydrochloric acid are added into a stannic chloride solution for ultrasonic treatment, then the stannic chloride solution is added into the mixed colloidal solution for ultrasonic mixing and standing to obtain a sol-gel coating solution, a titanium substrate is coated with the sol-gel coating solution, drying and sintering are performed, and the titanium anode is obtained. The invention further discloses the titanium anode prepared through the preparation method and application of the titanium anode in zinc electrodeposition. Compared with a titanium anode surface prepared by a thermal decomposition method, the titanium anode surface prepared by the sol-gel method is finer and more uniform in crystal grain, fine and uniform in surface crack, larger in specific surface area and better in electro-catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium electrodes, and in particular relates to an IrO2-RuO2-SnO2 / Ti coated titanium anode and a preparation method and application thereof. Background Art

[0002] Titanium electrodes have the advantages of light weight, good conductivity, strong corrosion resistance, high mechanical strength, and long service life. Their excellent resistance to wet chlorine is unmatched by other metal materials. However, there are no reports on their application in acidic oxygen evolution environments. The reason is that no titanium electrode coating material with excellent performance and economical cost has been developed.

[0003] The composition and structure of coating materials are one of the most important factors that determine the performance of electrodes. Therefore, once the titanium anode was introduced, a large amount of research work was carried out around the coating. One of the purposes is to seek synergistic effects through multi-component materials, so that the components can achieve close electronic connections and improve the electrode catalytic activity. Related studies have shown that IrO2 has good oxygen evolution catalytic activity, and can maintain high stability in the oxygen evolution environment, and has a low oxygen evolution overpotential; RuO2 has excellent electrochemical properties, chemical stability and catalytic activity, but its resistance to acid corrosion is poor. Therefore, in the oxygen evolution environment, IrO2-RuO2 titanium electrodes are mainly used, but IrO2 and RuO2 are both rare and precious metal materials with high raw material costs; the coating material has a low bonding strength with the titanium substrate and is prone to peeling and failure during operation; IrO2 and RuO2 form large intercrystalline gaps, acid solutions are easy to penetrate, resulting in short service life and other problems. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes an IrO2-RuO2-SnO2 / Ti coated titanium anode and a preparation method and application thereof.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] An IrO2-RuO2-SnO2 / Ti coated titanium anode, comprising a titanium substrate and a metal oxide coating;

[0007] The molar ratio of Ir, Ru and Sn in the metal oxide coating is (27.9-29.7):(65-69):(1-7).

[0008] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode comprises the following steps:

[0009] (1) adding a mixed solution of citric acid and ethylene glycol to a mixed solution of ruthenium trichloride and chloroiridic acid, then dropwise adding water and hydrochloric acid and performing ultrasonic treatment to obtain a mixed colloidal solution;

[0010] (2) Add citric acid and ethylene glycol to the tin tetrachloride solution for ultrasonic treatment, then add them to the mixed colloidal solution for ultrasonic mixing, let stand to obtain a sol-gel coating solution, apply the sol-gel coating solution to a titanium substrate, dry and sinter, to obtain the IrO2-RuO2-SnO2 / Ti coated titanium anode.

[0011] Beneficial Effects: Sn 4+ The ionic radius of Ir 4+ 、Ru 4+ 、Ti 4+ The ionic radius of Ir and Ru oxides is similar, and their oxides have the same rutile crystal structure, which makes it easier for them to form a rutile solid solution structure. SnO2 has high conductivity, high mechanical strength, good corrosion resistance, good oxygen evolution selectivity, and stable chemical properties, and can be firmly combined with the Ti matrix. Therefore, adding SnO2 to Ir and Ru oxide coatings can increase the activity of the coatings, improve the corrosion resistance of the coatings, and thus improve the comprehensive performance of the titanium anode.

[0012] Preferably, the mixed solution of ruthenium trichloride and chloroiridic acid in step (1) is obtained by dissolving ruthenium trichloride and chloroiridic acid in anhydrous ethanol and subjecting the mixture to ultrasonic treatment for 10 minutes; and / or,

[0013] The mixed solution of citric acid and ethylene glycol is obtained by dissolving citric acid and ethylene glycol in anhydrous ethanol and subjecting the mixture to ultrasonic treatment for 10 minutes, wherein the ratio of the added amounts of citric acid, ethylene glycol and anhydrous ethanol in the mixed solution of citric acid and ethylene glycol is 1 g:5 mL:5 mL.

[0014] Among them, the purity of citric acid is ≥99.5%; the purity of ethylene glycol is 99%.

[0015] Beneficial effects: The anode coating is prepared by thermal decomposition or sol-gel method, and the main difference between the two is the material mixing method and effect. IrO2 can maintain high stability in an oxygen evolution environment, and the oxygen evolution overpotential is low; RuO2 has excellent electrochemical properties, chemical stability and high catalytic activity; SnO2 has a certain catalytic activity, and can also improve the conductivity of the coating, refine the coating crystal structure, and is cheaper than Ir and Ru; IrO2, RuO2, SnO2 and other oxides are fully mixed, and the corresponding oxides are obtained after heat treatment to use the oxide structural defects and multivalent states to play a redox catalytic effect, but there are problems such as uneven distribution of oxide particles and insufficient reaction, resulting in uncontrollable reaction product yield, grain size, and intercrystalline gaps. Therefore, the titanium electrode prepared by direct thermal decomposition has low catalytic activity and short service life, while the sol-gel method can avoid the above-mentioned shortcomings of the titanium electrode prepared by direct thermal decomposition.

[0016] Preferably, the concentration of the tin tetrachloride solution in step (1) and step (2) is 5-15 g / L.

[0017] Preferably, the sintering temperature in step (1) and step (2) is 400-500° C. and the sintering time is 10 min.

[0018] Preferably, the coating amount is 1.0-3.0 mg / cm 2 .

[0019] Preferably, the ultrasonic treatment time in step (1) is 4 hours; and / or,

[0020] Preferably, the ultrasonic treatment time in step (2) is 10 minutes, and the ultrasonic mixing time is 1 hour.

[0021] Application of an IrO2-RuO2-SnO2 / Ti coated titanium anode in zinc electrowinning.

[0022] Compared with the prior art, the present invention has the following advantages and technical effects:

[0023] The present invention selects Ir and Ru as coating matrix elements and Sn as the main added element to obtain an IrO2-RuO2-SnO2 / Ti coated titanium anode. The addition of Sn in the present invention can reduce the grain size of the oxide coating, improve the anode catalytic activity, and promote the occurrence of oxygen evolution reaction. Compared with the pyrolysis method, the titanium anode surface grains prepared by the sol-gel method in the present invention are finer and more uniform, the surface cracks are fine and uniform, the specific surface area is larger, and it has better electrocatalytic activity, and is more suitable for preparing titanium anode coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0025] Figure 1 X-ray diffraction (XRD) patterns of the titanium anode coatings obtained in Examples 1-7 and Comparative Examples 2-4;

[0026] Figure 2 The scanning electron microscope (SEM) photos of the titanium anode coatings obtained in Examples 1-7 and Comparative Examples 2-4;

[0027] Figure 3 Cyclic voltammetry (CV) spectra of the titanium anode coatings obtained in Examples 1-7 and Comparative Examples 2-4;

[0028] Figure 4 The linear sweep voltammetry (LSV) spectra of the titanium anode coatings obtained in Examples 1-7 and Comparative Examples 2-4;

[0029] Figure 5 The Nyquist diagram and equivalent circuit diagram of the titanium anode coating obtained in Examples 1-7 and Comparative Examples 2-4;

[0030] Figure 6 The enhanced service life test of the titanium anodes obtained in Examples 1-7 and Comparative Examples 2-4;

[0031] Figure 7 LSV diagram of the titanium anode coating obtained by changing the coating amount in step (5) of Example 1;

[0032] Figure 8 CV diagram of the titanium anode coating obtained by changing the coating amount in step (5) of Example 1;

[0033] Fig. 9 The voltammetric charge of the titanium anode coating obtained by changing the coating amount in step (5) of Example 1. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0036] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;

[0037] The titanium substrate is: a TA2 titanium plate with a size of 30 mm × 10 mm × 3 mm. The titanium plate is polished with sandpaper to remove the surface oxide layer, and the polished titanium plate is placed in a 5% Na2CO3 solution at 60°C for 1 hour, and then the alkali-washed titanium plate is rinsed with deionized water and placed in a 10% oxalic acid solution for etching at a slightly boiling state for 2.5 hours, and finally ultrasonically treated for 10 minutes, fished out and rinsed with deionized water, dried and immersed in anhydrous ethanol for standby use;

[0038] The hydrochloric acid used had a concentration of 36-38%, purchased from Chengdu Kelong Chemical Reagent Factory;

[0039] Ruthenium trichloride (containing 40% Ru) was purchased from Kunming Boxi Metal Materials Co., Ltd.;

[0040] Chloroiridic acid (containing 35% Ir) was purchased from Kunming Boxi Metal Materials Co., Ltd.

[0041] Tin tetrachloride (analytical grade) was purchased from Xilong Chemical Co., Ltd.;

[0042] Oxalic acid (analytical grade) was purchased from Xilong Chemical Co., Ltd.

[0043] Citric acid purity ≥99.5%;

[0044] The purity of ethylene glycol is 99%.

[0045] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.

[0046] In the following embodiments, due to the certain loss of the coating liquid during the coating preparation process, the molar ratio of Ir, Ru and Sn raw materials in the coating preparation process is not exactly the same as the molar ratio of Ir / Ru / Sn in the coating. This is a normal phenomenon, and those skilled in the art can adjust the amount of raw materials added to the coating liquid according to conventional technical means to obtain a coating with a specified Ir / Ru / Sn molar ratio.

[0047] Example 1

[0048] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode comprises the following steps:

[0049] (1) According to the designed Ru / Ir molar ratio of the coating of 67.9:29.1, 0.0132 g of ruthenium trichloride and 0.0127 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0050] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0051] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0052] (4) According to the designed coating Ru / Ir / Sn molar ratio of 67.9:29.1:3, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes, and then a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain liquid No. 4, and then liquid No. 4 was slowly added to liquid No. 3 under ultrasonic conditions and ultrasonicated for 1 hour, and then allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0053] (5) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 2 mg / cm2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0054] Example 2

[0055] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode comprises the following steps:

[0056] (1) According to the designed Ru / Ir molar ratio of the coating of 69.3:29.7, 0.0101 g of ruthenium trichloride and 0.00969 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0057] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0058] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0059] (4) According to the designed coating Ru / Ir / Sn molar ratio of 69.3:29.7:1, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes, and then a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain liquid No. 4, and then liquid No. 4 was slowly added to liquid No. 3 under ultrasonic conditions and ultrasonicated for 1 hour, and then allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0060] (5) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, with a coating amount of 1.5 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0061] Example 3

[0062] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode comprises the following steps:

[0063] (1) According to the designed Ru / Ir molar ratio of the coating of 68.6:29.4, 0.013321 g of ruthenium trichloride and 0.012801 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0064] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0065] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0066] (4) According to the designed coating Ru / Ir / Sn molar ratio of 68.6:29.4:2, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes, and then a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain liquid No. 4, and then liquid No. 4 was slowly added to liquid No. 3 under ultrasonic conditions and ultrasonicated for 1 hour, and then allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0067] (5) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 2 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 500℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0068] Example 4

[0069] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode comprises the following steps:

[0070] (1) According to the designed Ru / Ir molar ratio of the coating of 67.2:28.8, 0.013065 g of ruthenium trichloride and 0.012555 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0071] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0072] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0073] (4) According to the designed coating Ru / Ir / Sn molar ratio of 67.2:28.8:4, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes, and then a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain liquid No. 4, and then liquid No. 4 was slowly added to liquid No. 3 under ultrasonic conditions and ultrasonicated for 1 hour, and then allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0074] (5) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 2 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 400℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0075] Example 5

[0076] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode comprises the following steps:

[0077] (1) According to the designed Ru / Ir molar ratio of the coating of 66.5:28.5, 0.012937 g of ruthenium trichloride and 0.012432 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0078] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0079] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0080] (4) According to the designed coating Ru / Ir / Sn molar ratio of 66.5:28.5:5, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes, and then a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain liquid No. 4, and then liquid No. 4 was slowly added to liquid No. 3 under ultrasonic conditions and ultrasonicated for 1 hour, and then allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0081] (5) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 2 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0082] Example 6

[0083] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode comprises the following steps:

[0084] (1) According to the designed Ru / Ir molar ratio of the coating of 65.8:28.2, 0.012809 g of ruthenium trichloride and 0.012309 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0085] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0086] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0087] (4) According to the designed coating Ru / Ir / Sn molar ratio of 65.8:28.2:6, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes, and then a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain liquid No. 4, and then liquid No. 4 was slowly added to liquid No. 3 under ultrasonic conditions and ultrasonicated for 1 hour, and then allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0088] (5) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 2 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0089] Example 7

[0090] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode comprises the following steps:

[0091] (1) According to the designed Ru / Ir molar ratio of the coating of 65.1:27.9, 0.012680 g of ruthenium trichloride and 0.012185 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0092] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;

[0093] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0094] (4) According to the designed coating Ru / Ir / Sn molar ratio of 65.1:27.9:7, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes. Then, a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain liquid No. 4. Then, liquid No. 4 was slowly added to liquid No. 3 under ultrasonic conditions and ultrasonicated for 1 hour. The solution was allowed to stand for more than 38 hours to obtain a sol-gel coating solution;

[0095] (5) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 2 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 400℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.

[0096] Comparative Example 1

[0097] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode, which is different from Example 1 in that it is prepared by a thermal decomposition method, and specifically comprises the following steps:

[0098] IrCl3, RuCl3 and SnCl4 were added to a mixed solvent (n-butanol and anhydrous ethanol were mixed in a volume ratio of 1:1) at a molar ratio of Ru / Ir / Sn of 67.9:29.1:3, and a coating solution was prepared by ultrasonic mixing treatment. The coating solution was evenly applied to the surface of the titanium substrate with a fine-bristled brush, and infrared irradiation was performed for 30 minutes until the coating solution was completely dry. The coating solution was then transferred to a muffle furnace and calcined at 450°C for 10 minutes. After natural cooling, the coating solution was applied again, infrared irradiation was performed, and calcination was performed. The above steps were repeated many times, and the last calcination time was 1 hour. After natural cooling, the electrode preparation was completed.

[0099] Comparative Example 2

[0100] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode, which is different from Example 1 in that the molar ratio of Ru / Ir / Sn is 64.4:27.6:8. The remaining process steps and parameters are the same as those in Example 1.

[0101] Comparative Example 3

[0102] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode is different from that in Example 1 in that the molar ratio of Ru / Ir / Sn is 63.7:27.3:9. The remaining process steps and parameters are the same as those in Example 1.

[0103] Comparative Example 4

[0104] A method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode is different from that in Example 1 in that the molar ratio of Ru / Ir / Sn is 7:3:0. The remaining process steps and parameters are the same as those in Example 1.

[0105] Application Example 1

[0106] Application of an IrO2-RuO2-SnO2 / Ti coated titanium anode in zinc electrowinning comprises the following steps:

[0107] A continuous zinc electroplating experiment of 24 hours was conducted on the titanium anodes obtained in Examples 1-7 and Comparative Examples 1-4. The experimental conditions are as follows: the anode is the titanium anode obtained in Examples 1-7 and Comparative Examples 1-4, the cathode is a pure aluminum plate, the electrolyte is a 55g / L Zn2SO4 solution, the electrolyte acidity is H2SO4 165g / L, the electrolytic cell temperature is 38°C to 40°C, the electrolysis time is 24 hours, and the electrolyte flow rate is 470mL / h.

[0108] Technical effect:

[0109] 1.XRD analysis

[0110] Figure 1 This is the XRD spectrum of the anode coating. It can be seen that the graph contains characteristic peaks related to Ti (PDF#65-3362) and rutile-type IrO2 (PDF#86-0330), RuO2 (PDF#70-2662) and SnO2 (PDF#72-1147). The characteristic peaks related to the titanium matrix mainly appear at 34.964°, 38.187°, 40.010°, 52.801° and 70.403°, and the characteristic peaks related to the rutile-type IrO2, RuO2 and SnO2 mainly appear near 27.841°, 34.964° and 52.801°. By comparing with the corresponding standard spectrum, it can be found that IrO2, RuO2 and SnO2 have obvious offset phenomena on the (110) and (101) crystal planes, indicating that there is a rutile-type structure (Ir Ru Sn)O2 solid solution in the coating. This is because Ru 4+ , Ir 4+ and Sn 4+ The ionic radii of the three oxides are 0.076nm, 0.077nm and 0.069nm respectively, and all three are rutile oxides. According to the Hume-Rothery theory, this mixed ternary oxide system can form a rutile solid solution. The lattice parameters of rutile RuO2 are calculated by Jade6.5 software. Higher than its standard value Lower lattice parameter than IrO2 and the lattice parameters of SnO2 It shows that IrO2 and SnO2 form a ruthenium-based rutile eutectic with RuO2. With the increase of SnO2 content, due to the existence of (Ir-Ru-Sn)O2 solid solution, the intensity of the relevant characteristic peaks first increases and then weakens, and the width gradually widens. From the relationship between the grain diameter and the diffraction peak width, it can be seen that the addition of Sn can affect the crystal structure of the coating material.

[0111] 2. Crystallinity

[0112] The crystallinity of the coating was calculated using Jade software, and the results are shown in Table 1.

[0113] Table 1 Anode coating ratio and crystal form calculation data

[0114] serial number sample Ir-Ru-Sn molar ratio Crystallinity % 0# Comparative Example 4 3:7:0 79.48 1# Example 2 29.7:69.3:1 82.39 2# Example 3 29.4:68.6:2 85.32 3# Example 1 29.1:67.9:3 85.65 4# Example 4 28.8:67.2:4 85.43 5# Example 5 28.5:66.5:5 88.39 6# Example 6 28.2:65.8:6 87.42 7# Example 7 27.9:65.1:7 88.53 8# Comparative Example 2 27.6:64.4:8 89.39 9# Comparative Example 3 27.3:63.7:9 90.88

[0115] It can be seen that with the increase of Sn addition, the crystallinity of the coating increases, indicating that the content of the generated (Ir-Ru-Sn)O2 solid solution increases, and the solid solution has good oxygen evolution characteristics and strong acid corrosion resistance. Since X-rays can penetrate the coating, the characteristic peaks of Ti exist in the XRD spectrum, and the characteristic peaks related to TiO2 do not appear, indicating that the titanium substrate is not oxidized.

[0116] 2. SEM analysis

[0117] Figure 2 The SEM image of the sample prepared by thermal decomposition method shows that dense and uneven cracks appear on the surface of the sample. This is due to the different thermal expansion and contraction coefficients of the coating and the titanium substrate, and the inconsistent expansion and contraction of the coating during heat treatment. At the same time, it can be clearly observed that with the increase of Sn addition, the cracks in the coating become sparse, the cracks become narrower and shallower, and the coating gradually tends to be flat, which once again proves that Sn has the property of refining the coating grains and flattening the coating surface. Figure 2 Starting from the 3# part, as the amount of Sn added increases, the number of cracks on the coating surface decreases significantly. By the 5# figure, the cracks on the coating surface are very sparse and the cracks are significantly narrowed, which is very beneficial to the stability and corrosion resistance of the coating. Figure 2 Starting from the 6# part, crystalline substances begin to appear on the coating surface with the increase of Sn addition amount. This may be the crystallization precipitation of (Ir Ru Sn)O2 solid solution or the precipitation of SnO2 crystals, which may have a certain effect on the catalytic activity and electrochemical performance of the coating. Figure 2 When the Sn addition amount is the largest in the 9# part, there are almost no cracks on the coating surface, the coating is relatively flat as a whole, and obvious stripes appear.

[0118] 3. Electrochemical performance test

[0119] 3.1 Cyclic voltammetry curve test

[0120] The cyclic voltammetry test results of Ti / IrO2-RuO2-SnO2 anode in 1 mol / L sulfuric acid solution are shown in Figure 3 As shown. The current response observed in the CV curve is caused by the charge transfer caused by the redox reaction on the surface of the active oxide. The broad peaks observed at a potential of -0.8 to 0.8 V are related to the redox transitions of Ir(IV) / Ir(V), Ru(II) / Ru(III), Ru(III) / Ru(IV), and Ru(IV) / Ru(V). In the potential range of 0 to 0.75 V, no oxygen evolution reaction and other side reactions occur at the electrode. The corresponding current is the charging current of the electrode double layer. The size of the area enclosed by the corresponding cyclic voltammetry curve can reflect the number of active sites on the electrode surface.

[0121] The voltammetric charge (q) obtained by integrating the CV curve can represent the electrochemically active surface area of ​​the coating. The calculation results are shown in Table 2.

[0122] Table 2 Calculation of voltammetric charge of different anode coatings

[0123]

[0124]

[0125] It can be seen from Table 2 that with the increase of Sn addition, the q outer There is no obvious regularity in the value, q total Value and q inner The value generally shows a decreasing trend. This is because the volt-ampere capacity of the electrode is directly related to the specific surface area of ​​the electrode. The larger the specific surface area, the more active sites, and the larger the volt-ampere capacity.

[0126] 3.2 Polarization curve test

[0127] Figure 4 The polarization curves of titanium anodes with different coatings are shown in Figure 2. The results show that the oxygen evolution potential of the anode increases with the increase of Sn addition, and the current density is 0.03A / cm 2 The oxygen evolution potentials of 0#~9# titanium anodes were 0.802V, 0.808V, 0.817V, 0.820V, 0.814V, 0.817V, 0.819V, 0.815V, 0.808V and 0.805V, respectively. The oxygen evolution potentials of several titanium anodes generally showed a trend of increasing first and then decreasing. Adding Sn can increase the oxygen potential of the titanium anode, but the oxygen evolution potential of the titanium anode will decrease with the increase of Sn, which is related to the crystal structure and surface activity of the titanium anode coating. It can also be seen from Table 1 that the addition of Sn can affect the content of amorphous substances in the titanium anode coating, thereby affecting the electrocatalytic activity and oxygen evolution potential of the coating electrode. The electrocatalytic activity of the (Ir-Ru-Sn)O2 solid solution formed by adding Sn is better than that of the individual oxides of SnO2, IrO2, and RuO2, and the solid solution formed has high stability, which is helpful for the corrosion resistance of the coating.

[0128] 3.3 Kinetic parameters

[0129] According to the Tafel formula η = a + logi anode polarization experimental results, a is the intercept of the Tafel curve, reflecting the difficulty of electrode electron transfer, and b is the slope. The relationship curve between η and logi was linearly fitted using Nova software to obtain a and b parameters and calculate the exchange current density (J0). The results are shown in Table 3.

[0130] Table 3 Kinetic parameters of anode coating

[0131] sample a(mV) b(mV / dec) <![CDATA[J0(A / cm)]]> 0# 85.12 15.63 <![CDATA[1.4707×10 -6 ]]> 1# 96.69 13.12 <![CDATA[1.5023×10 -6 ]]> 2# 109.45 40.58 <![CDATA[2.3460×10 -6 ]]> 3# 115.45 32.16 <![CDATA[2.2324×10 -5 <!-- 8 -->]]> 4# 110.72 23.03 <![CDATA[1.7574×10 -5 ]]> 5# 92.86 20.06 <![CDATA[2.3084×10 -6 ]]> 6# 88.92 24.88 <![CDATA[2.1320×10 -6 ]]> 7# 76.81 24.56 <![CDATA[1.8986×10 -6 ]]> 8# 67.05 20.70 <![CDATA[1.2207×10 -6 ]]> 9# 68.26 14.41 <![CDATA[1.0121×10 -6 ]]>

[0132] It can be seen that the Tafel slope value b first increases and then decreases with the increase of Sn addition, which indicates that the electrocatalytic activity of the anode first increases and then decreases with the increase of Sn addition, which is consistent with the results of the anode polarization experiment. The J0 value first increases and then decreases with the increase of Sn addition, and reaches the maximum value when the Sn content is 2%, indicating that the electrode is not easy to polarize at this time and oxygen evolution reaction is easy to occur. When the Sn addition amount is ≥7%, Sn has a weakening effect on the polarization performance of the Ti / IrO2-RuO2-SnO2 anode. The above results show that the addition of Sn has limited effect on improving the polarization performance of the Ti / IrO2-RuO2-SnO2 anode, but can reduce the use of precious metals such as iridium and ruthenium.

[0133] 3.4 AC impedance test

[0134] Figure 5 The Nquist diagram and equivalent circuit diagram of the anode coating. The equivalent circuit of the oxygen evolution reaction of the coated titanium anode in the acidic solution can be expressed by Rs(R f Q l )(R ct Q dl ) is fitted, where Rs represents the electrolyte resistance, R f represents the film resistance of the metal oxide coating, R ct It represents the charge transfer resistance during the oxygen evolution reaction at the electrode, Q l represents the surface film resistance of the oxide coating, Q dl represents the double layer capacitance, (R f Q l ) represents the anode coating’s own impedance, (R ct Q dl ) represents the impedance between the anode coating and the interface. The oxygen evolution reaction of the coated titanium anode in sulfuric acid solution mainly occurs at the active center on the surface of the oxide coating. First, the active substance S contacts and reacts with H2O in the solution, releasing electrons and generating the intermediate product S-OH. ads , that is, S+H2O→S-OH ads +H + +e - ; As the potential increases, the intermediate product continues to release electrons to generate another new intermediate product SO ads , namely S-OH ads →SO ads +H + +e - ; Finally, the intermediate product SO ads It is reduced to the original active substance S and releases O2 at the same time, i.e. 2S-O ads →2S+O2. Figure 5It can be seen that the equivalent circuit is a fit of two time constants, which is related to the cracks and porosity of the coating surface.

[0135] Table 4 shows the EIS parameters of titanium anodes with different coatings. It can be seen from the table that the addition of Sn can significantly reduce the film resistance R of the metal oxide coating. f , for the charge transfer resistance R ct The effect is not significant. This indicates that the addition of Sn mainly improves the electrocatalytic activity of the coating anode by reducing the oxygen evolution reaction potential of the coating and increasing the conductivity of the anode coating.

[0136] Table 4 EIS parameters of anode coating

[0137]

[0138] 4. Strengthen service life test

[0139] In order to determine the service life of the coated titanium anode, in a 1 mol / L sulfuric acid solution, 1 A / cm 2 The enhanced failure test was carried out at a constant current density of . Figure 6 The results of the intensive service life test are given.

[0140] from Figure 6 It can be seen that the enhanced service life of the IrO2-RuO2-SnO2 / Ti anode increases with the increase of Sn addition. When the Sn addition is greater than 3%, the enhanced service life curve begins to flatten. This is mainly because the addition of Sn can significantly refine the coating grains and reduce cracks. At the same time, the generated (Ir-Ru-Sn)O2 solid solution has a highly stable structure and catalytic performance. When the Sn addition is greater than 3%, the (Ir-Ru-Sn)O2 solid solution gradually approaches the maximum, and the coating surface tends to be flat (from Figure 2 The oxide coating becomes more and more dense and has a stronger ability to resist acid corrosion, thereby extending the service life of the anode in sulfuric acid solution.

[0141] 5. Analysis of the influence of coating amount on titanium anode coating

[0142] 5.1 Figure 7 The linear sweep voltammetry (LSV) diagram of the coating at different coating amounts in step (5) of Example 1 is shown. It can be seen from the figure that the potential of the anode of the coating with different coating amounts is not much different, all between 0.81V and 0.82V. By comparing the slopes of the curves, it can be clearly observed that the coating content is 1.0mg / cm 2 The electrode current density of the coated titanium anode is the largest when the electrode voltage is the same in the polarization curve, indicating that the electrode polarization degree of the coated anode is the smallest during the oxygen evolution reaction. 2The polarization degree of the coated titanium anode is the largest. In summary, the coating content is 1.0 mg / cm 2 The Ti / Ir-Ru-Sn (3%) anode has a smaller degree of polarization during the reaction and has the best performance.

[0143] 5.2 Cyclic voltammetry curve test

[0144] To further explore the effect of coating amount on the electrochemical performance of Ir-Ru-Sn (3%) / Ti anode, a cyclic voltammetry (CV) curve test was carried out in a 1 mol / L H2SO4 solution at a constant potential. The test conditions were: scan rate 5 mV / s, voltage range -0.8 V ~ 0.8 V. The test results are shown in Figure 2. Figure 8 shown.

[0145] exist Figure 8 The current response observed in the graph is due to the charge transfer caused by the redox reaction on the surface of the active oxide. The broad peaks observed at the potential of -0.8 to 0.8 V are related to the redox transitions of Ir(IV) / Ir(V), Ru(II) / Ru(III), Ru(III) / Ru(IV), and Ru(IV) / Ru(V). In the potential range of 0 to 0.80 V, no oxygen evolution reaction and other side reactions occur at the electrode. The corresponding current is the charging current of the electrode double layer. The size of the area enclosed by the corresponding cyclic voltammetry curve can reflect the number of active sites on the electrode surface.

[0146] The voltammetric charge obtained by integrating the CV curve can represent the electrochemically active surface area of ​​the coating. The calculation results are as follows Fig. 9 shown.

[0147] Fig. 9 The voltammetric charge of the Ir-Ru-Sn (3%) / Ti anode coating with different coating amounts is given. As the coating amount increases, the voltammetric charge of the anode coating is 354.74 mC·cm -2 、301.58mC·cm -2 、214.14mC·cm -2 、116.88mC·cm -2 and 253.88 mC·cm -2 As the coating content increases, there is no obvious regularity in the voltammetric charge on the coating surface, which is consistent with the CV test results. Because the voltammetric charge of the electrode is directly related to the number of catalytic active sites on the electrode surface, a large voltammetric charge indicates that there are many catalytic active sites on the electrode surface, which is beneficial to improving the efficiency of the oxygen evolution catalytic reaction. By comparison, it can be seen that the coating content is 1.0 mg / cm 2The voltammetric charge on the surface of the Ir-Ru-Sn(3%) / Ti anode is the largest, indicating that the surface of the coated anode contains more oxygen evolution catalytic active sites and has better oxygen evolution catalytic reaction performance.

[0148] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. An IrO2-RuO2-SnO2 / Ti coated titanium anode, characterized in that: including a titanium substrate and a metal oxide coating; The molar ratio of Ir, Ru and Sn in the metal oxide coating is (25-30):(65-70):(1-7).

2. The method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode according to claim 1, characterized in that: The following steps are involved: (1) adding a mixed solution of citric acid and ethylene glycol to a mixed solution of ruthenium trichloride and chloroiridic acid, then dropwise adding water and hydrochloric acid and performing ultrasonic treatment to obtain a mixed colloidal solution; (2) Add citric acid and ethylene glycol to the tin tetrachloride solution for ultrasonic treatment, then add them to the mixed colloidal solution for ultrasonic mixing, let stand to obtain a sol-gel coating solution, apply the sol-gel coating solution to a titanium substrate, dry and sinter, to obtain the IrO2-RuO2-SnO2 / Ti coated titanium anode.

3. The method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode according to claim 2, characterized in that: The mixed solution of ruthenium trichloride and chloroiridic acid in step (1) is obtained by dissolving ruthenium trichloride and chloroiridic acid in anhydrous ethanol and subjecting the mixture to ultrasonic treatment for 10 minutes.

4. The method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode according to claim 2, characterized in that: The mixed solution of citric acid and ethylene glycol in step (1) is obtained by dissolving citric acid and ethylene glycol in anhydrous ethanol and subjecting them to ultrasonic treatment for 10 minutes; and / or, In the mixed solution of citric acid and ethylene glycol, the ratio of the added amounts of citric acid, ethylene glycol and anhydrous ethanol is 1 g:5 mL:5 mL.

5. The method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode according to claim 2, characterized in that: The concentration of the tin tetrachloride solution in step (2) is 5-15 g / L.

6. The method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode according to claim 2, characterized in that: The sintering temperature in step (2) is 400-500° C. and the sintering time is 10 minutes.

7. The method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode according to claim 2, characterized in that: The coating amount in step (2) is 1.0-3.0 mg / cm 2 .

8. The method for preparing an IrO2-RuO2-SnO2 / Ti coated titanium anode according to claim 2, characterized in that: The ultrasonic treatment time in step (1) is 4 hours; and / or, The ultrasonic treatment time in step (2) is 10 minutes, and the ultrasonic mixing time is 1 hour.

9. Use of an IrO2-RuO2-SnO2 / Ti coated titanium anode as claimed in claim 1 in zinc electrowinning.